From metabolic connectivity to molecular connectivity: application to dopaminergic pathways. - Verger, Antoine; Horowitz, Tatiana; Chawki, Mohammad B.; Eusebio, Alexandre; Bordonne, Manon; Azulay, Jean-Philippe; Girard, Nadine; Guedj, Eric (European Journal of Nuclear Medicine & Molecular Imaging, 2020)
Introduction: This study aims to reveal the feasibility and potential of molecular connectivity based on neurotransmission in comparison with the metabolic connectivity with an application to dopaminergic pathways. For this purpose, we propose to compare the neurotransmission connectivity findings using 123I-FP-CIT SPECT and 18F-FDOPA PET with the metabolic connectivity findings using 18F-FDG PET. Methods: 18F-FDG PET and 123I-FP-CIT SPECT images from 47 subjects and 18F-FDOPA PET images from 177 subjects, who had no neurological or psychiatric disorders, were studied. Interregional correlation analyses were performed at the group level to determine the midbrain's connectivity via glucose metabolic rate using 18F-FDG PET and via dopaminergic binding potential using 123I-FP-CIT SPECT and 18F-FDOPA PET. SPM-T maps of each radiotracer were generated, and masks used to highlight the significant differences obtained among the imaging modalities and targets. Results: The three dopaminergic pathways (i.e., nigrostriatal, mesolimbic, and mesocortical) were identified by 18F-FDG PET (1599 voxels, with a Tmax value of 12.6), 123I-FP-CIT SPECT (1120 voxels, with Tmax value of 5.1), and 18F-FDOPA PET (6054 voxels, with Tmax value of 11.7) for a T voxel threshold of 5.10, 2.80, and 5.10, respectively. Using the same T voxel threshold of 5.10, 18F-FDOPA PET showed more specific findings than 18F-FDG PET with less voxels identified outside these pathways (− 9323 voxels), whereas no significant voxels were obtained with 123I-FP-CIT SPECT at this threshold. Conclusion: The present study illustrates the feasibility and interest in using molecular connectivity with 18F-FDOPA PET for dopaminergic pathways. Such analyses could be applied to specific diseases involving the dopaminergic system.